PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KEPALA BERNOMOR STRUKTUR UNTUK MENCAPAI KETUNTASAN BELAJAR - Joni Susilowibowo, ; Lika Yuliati, (Pendidikan Ekonomi, 2009)
The research was aimed at finding out (1) how the teachers competence was in managing the classroom and the students activity, (2) how the improvement of the students achievement was, and (3) how the students response to the structured number head type was. The subject of the study was the accounting teacher and 56 students in his class. The instruments of the study consisted of observation sheet, test and questionare. The data obtained were analyzed descriptively. The result of the study was that the teachers competence in managing the class improved in every cycle. The students activity was considered quite good. In addition, the achievement increased as well. Thus, it can be concluded that the application of cooperative learning model was joyful for the students.